(untitled) (KYAMC Journal, 2026)
Background: COVID-19 infection caused by the new coronavirus was reported in December by the World Health Organization 2019 in China. The main clinical manifestations of infected patients are fever, cough, and dyspnea. Musculoskeletal symptoms, including myalgia, arthralgia, and fatigue, are nearly constantly present. Objective: To evaluate the musculoskeletal symptoms and their relationship with disease severity in patients with COVID-19 infection attending a tertiary-level hospital in Bangladesh. Materials and Methods: This cross-sectional study, conducted at Dhaka Medical College Hospital, Bangladesh, aimed to evaluate the prevalence of musculoskeletal symptoms and their relationship with disease severity in 113 patients with RT-PCR-confirmed COVID-19. Results: The findings revealed that musculoskeletal manifestations were highly common, present in 82.3% of the patients. The most frequent symptoms were fatigue (77.4%) and myalgia (67.7%), followed by arthralgia (22.6%). The study further established a significant relationship between fatigue and the severity of the COVID-19 illness. Additionally, a notable gender disparity was observed, with female patients reporting significantly higher psychological fatigue scores compared to males. Conclusion: The research concludes that musculoskeletal symptoms, particularly fatigue and myalgia, are predominant clinical features in COVID-19 patients. The association of fatigue with disease severity and its higher prevalence in females underscores the need for clinicians to recognize these symptoms.